Do natural gas and renewable energy consumption lead to less CO2 emission? Empirical evidence from a panel of BRICS countries. (15th December 2017) - Dong, Kangyin; Sun, Renjin; Hochman, Gal
Abstract: This study is the first attempt to investigate the nexus among per capita carbon dioxide (CO2 ) emissions, gross domestic product (GDP), and natural gas and renewable energy consumption within the framework of the environmental Kuznets curve (EKC), in a 1985–2016 sample of BRICS countries (i.e., Brazil, Russia, India, China, and South Africa). For this purpose, panel unit root, cointegration, and causality tests allowing for cross-sectional dependence are conducted. Employing the augmented mean group (AMG) estimator, the results provide strong evidence in favor of the EKC hypothesis for the BRICS countries by proposing that the EKC holds in all five BRICS countries; the turning points (TPs) lie between 4282.90 (India) and 16, 553.77 (China), while the turning years (TYs) are estimated to be between 2018 (Russia) and 2035 (India). Furthermore, increasing natural gas and renewable energy consumption lowers CO2 emissions, which indicates that, 1% increase in natural gas and renewable energy consumption for the BRICS countries will decrease CO2 emissions by 0.1641% and 0.2601%, respectively. The causality analysis underscores feedback hypothetical links among CO2 emissions, natural gas consumption, and renewable energy consumption in the long run. Some policy implications are highlighted for BRICS countries' policymakers not only for tackling CO2 emissions, but also for promoting growth in the natural gas and renewable energy industries. Highlights: Role of natural gas and renewables in mitigating CO2 emissions in BRICS countries. Presence of environmental Kuznets curve supported in the data. The introduction of both natural gas and renewables mitigates CO2 emissions. Short- and long-run bidirectional causality between natural gas and CO2 . Short- and long-run bidirectional causality between renewables and CO2 .